Mendeteksi Kemacetan Jalan di DIY dengan Mengkaji Kapasitas dan Kinerja Ruas Jalan Menggunakan PKJI 2023 - Heriadi Heriadi; Ninik Ariyani; Hendrik Pratama Bezawato Hia; Aprilia Priskila Pigome; Nikolas Indra Wijaya; Yolan Benediktus Halawa (Institut Teknologi Garut, 2026)
The average motor vehicle density per kilometer in DIY falls into the high-density category, indicating a high potential for traffic congestion in DIY. This study aims to detect road congestion in DIY by analyzing the capacity and performance of road sections using the 2023 Indonesian Road Capacity Index (PKJI). The analysis results indicate two road sections with a high potential for congestion: the Jogja-Solo Road and the Besi Jangkang Road. The road with the highest capacity is the Janti Road, while the one with the lowest capacity is the Pakem-Prambanan Road. A saturation level > 0.85 occurs on the Jogja-Solo and Besi Jangkang roads. This study contributes to the development of transportation studies in DIY and the application of the 2023 PKJI in identifying road sections with a high potential for congestion, thereby serving as a basis for more effective transportation planning and management. The contribution of this study is to provide important information for improving transportation efficiency and safety in DIY.